Influence of microstructural heterogeneities on small-scale mechanical properties of an additively manufactured Al-Ce-Ni-Mn alloy - Tanvi Ajantiwalay; Richard Michi; Christian Roach; Amit Shyam; Alex Plotkowski; Arun Devaraj (Additive Manufacturing Letters, 2022)
Laser powder bed fusion-based additive manufacturing (AM) is a promising method to fabricate creep-resistant Al-rare earth alloys (Al-Ce-Ni-Mn) with stable microstructures at up to 400 °C. However, creep testing of these alloys at high temperatures shows that void coalescence and failure initiation occurs along the melt pool boundaries in the microstructure. Hence it is crucial to understand how the local mechanical behavior of the melt pool boundaries would influence the global properties of the AM produced alloy. In this study, in situ nanoindentation conducted at room temperature and 300 °C revealed a reduced hardness at the melt pool boundaries. Similarly, micro-pillar compression showed a slight decline in yield strength at these boundaries, indicating that they are the weak spots in the microstructure. Such multimodal local mechanical property studies are necessary for understanding the influence of melt pool boundaries on the bulk response of fusion-based AM alloys.